Information Management Project at the School of Library and Information Sciences of the University of Costa Rica as support for continuous improvement processes - Calvo Guillén, Ginnette Carolina (2023)
The first phase of an information management project was carried out at the School of Library and Information Sciences of the University of Costa Rica, from 2019 to 2021. The project was created as a response to the weaknesses identified in the self-assessment process of 2007-2011, among which stand out: weaknesses in the use and dissemination of information, a weak archive system that has not been managed or updated correctly and the lack of specific policies for the handling of files. The project is approached from a qualitative approach and seeks to describe the way in which information management is developed in the School, while providing contributions that allow strengthening the processes developed. It contemplates three stages: information mapping, policy definition and training of the actors involved in information management. Among the main achievements, the improvement in the systematization and management of information stands out; as well as the strengthening of internal communication. This is reflected in the implementation of an automated document management system, a process manual, and the training of teaching and administrative staff in document management. It concluded the need to involve different actors in the process; as well as working hand in hand with professionals from other disciplines. Finally, the importance of having qualified human resources as a key element for the quality of documentary processes is pointed out.